Electrospun Composite Liquid Crystal Elastomer Fibers - Sharma, Anshul (Materials (Basel), 2018)
We present a robust method to prepare thin oriented nematic liquid crystalline elastomer-polymer (LCE-polymer) core-sheath fibers. An electrospinning setup is utilized to spin a single solution of photo-crosslinkable low molecular weight reactive mesogens and a support polymer to form the coaxial LCE-polymer fibers, where the support polymer forms the sheath via in situ phase separation as the solvent evaporates. We discuss the effect of phase separation and compare two different sheath polymers (polyvinylpyrrolidone and polylactic acid), investigating optical and morphological properties of obtained fibers, as well as the shape changes upon heating. The current fibers show only irreversible contraction, the relaxation most likely being hindered by the presence of the passive sheath polymer, increasing in stiffness on cooling. If the sheath polymer can be removed while keeping the LCE core intact, we expect LCE fibers produced in this way to have potential to be used as actuators, for instance in soft robotics and responsive textiles.